Formação continuada de professores de língua inglesa: em busca de uma prática pedagógica multiletrada para a EJA - Brum, Maísa Helena (2019)
A collaborative practice within school contexts is understood as a “systematized and mediated activity between subjects, based on instruments that enable knowledge construction and the development of autonomy” (NININ, 2008, p. 21). In this sense, this paper aims to investigate to what extent a proposal for a continuing and collaborative education promotes the construction of a multiliterate pedagogical practice in English language in a public-school context, particularly for youth and adult education. The research was carried out with two teachers of English working with Youth and Adult Education (EJA, in Portuguese) at two different public schools in the city of Santa Maria, located in the state of Rio Grande do Sul, Brazil. These teachers were participants in a continuing education program associated with the umbrella project "Multiletramentos, Interdisciplinaridade e Formação de Professores de Linguagem na Escola”, developed by the Postgraduate Course in Linguistics in the Federal University of Santa Maria (UFSM, in Portuguese). The continuing education program focused on reflection about the teaching practice of the language teacher, the construction of collaborative practices, and also the production of teaching units based on the Pedagogy of Multiliteracies (KALANTZIS et al., 2016). The program consisted of four moments: 1) theoretical discussions about the Pedagogy of Multiliteracies; 2) practical workshops for the production of teaching material for the EJA; 3) teaching practice in the classroom; and, finally, 4) Self-Confrontation sessions on the multiliterate practice developed in the participants’ classrooms. Regarding the methodological tools, at first, semi-structured interviews were conducted in order to understand participants’ initial representations of language teaching and language learning. These data were analyzed based on the ideational and logical metafunctions of the Systemic-Functional Grammar (SFG). Afterwards, reflective sessions were developed with the participants, these sessions were recorded in audio and later, transcribed. The analysis of the transcription of audio records were conducted through epistemic-argumentative actions developed by the Center for Collaborative Studies in School Contexts (N.E.C.C.E, in Portuguese), from UFSM. The analysis of the epistemic-argumentative actions among the participants aimed to understand the collaborative-argumentative process established between them, concerning the development of a multiliterate practice in English for the context of EJA. Thus, it is understood that the collaborative-argumentative process in this teacher education program guided the construction of critical and reflective thinking by the participants, as well as expanded the “possibilities of enhancing understanding” (NININ, 2018, p. 104) of concepts related to the Pedagogy of Multiliteracies. Concerning the production of didactic units, they were organized and developed based on the knowledge processes proposed by the Pedagogy of Multiliteracies: “Experiencing, Analyzing, Conceptualizing and Applying” (COPE; KALANTZIS, 2015). In this sense, the production of the didactic units and teachers’ reflection upon the material demonstrated that they improved their pedagogical planning from the perspective of the Pedagogy of Multiliteracies, turning their practice into a more meaningful, relevant and contextualized environment for their students.